The Quality of Early Childhood Curricula and Distributed Leadership in Lithuanian ECEC Institutions - Agne Brandisauskiene; Jurate Cesnaviciene; Milda Bredikyte; Regina Sabaliauskiene (Education Sciences, 2024)
The early childhood curriculum is an integral part of the educational process, and many countries are looking at how to ensure its quality. With the decentralization of educational content in Lithuania, each Early Childhood Education and Care (ECEC) institution develops its own curriculum. In this case, the role of the head teacher at school and the leadership style they adopt become very important. Our study aims to investigate the expression of shared leadership in Lithuanian preschool education institutions and how it relates to the curriculum quality. An online survey was conducted in spring–autumn 2023. The sample was randomly selected from a list of kindergartens (N = 549) operating in Lithuania, and 133 kindergartens were selected. Of these, 79 (59.4%) institutions responded and agreed to participate. The research sample comprised 461 early childhood educators. The analysis of the survey data showed that distributed leadership can explain 61.3% of the quality of the curriculum. This means that if there is a higher degree of distributed leadership in the early childhood education community, the quality of the ECEC curriculum will likely be higher. ECEC leaders should pay attention to the individual scales of distributed leadership, collaboration, and cooperation.